Box, cable and smartphone: a simple laparoscopic trainer. (1st July 2015) - Lee, Migie; Savage, Jason; Dias, Maxwell; Bergersen, Philip; Winter, Matthew
Summary: Background: Laparoscopic surgery requires different abilities to open surgery, and is challenging to learn within the confines of the operating theatre. With the development of laparoscopic surgery in modern surgery, the importance in improving these skills is becoming an increasing focus of surgical training programmes. Context: The assembly of the laparoscopic trainer and exercises was performed at the University of Sydney Clinical School located at Hornsby Hospital in Sydney, Australia. The objective was to design and construct a new concept smartphone box laparoscopic trainer that is affordable and replicable, and to demonstrate its usefulness in practising laparoscopic techniques to improve skills outside of the operating theatre. Innovation: The trainer was constructed using a personal smartphone, cardboard box, video graphics array (VGA) adaptor, VGA cable and a computer screen. Laparoscopic instruments and materials used for simulated task exercises were obtained from the operating theatre. Simulated demonstrations of simple laparoscopic tasks included suture handling, instrument knot‐tying and anastomotic suture techniques. Implications: The smartphone box trainer is inexpensive (approximately $60) and took less than 20 minutes to build. The cost was almost entirely for the VGA adaptor. The box trainer was light, portable and easily transported to any setting that provided a computer screen. It is an inexpensive, easy‐to‐assemble, replicable model that benefits from the advanced technology of personal smartphones, and can be easily accessed as a useful tool in learning and improving laparoscopic techniques. Laparoscopic surgery requires different abilities to open surgery